Evaluación de la preferencia sensorial en tres marcas de gelatinas de venta en el mercado de trujillo, 2013 - Del Aguila Castillo, Fernando (2014)
Sensory analysis is a useful discipline to know the organoleptic properties of foods, as well as pharmaceutical products, cosmetics, etc.., Through the senses, what is innate in man and that from the moment a product is tested, it is a trial about it, if you like or dislike, and describes and recognizes its characteristic flavor, odor, texture, etc. It is important that the senses are well developed to give an objective and subjective outcome. The purpose of this study is to determine the brand of commercial gelatine with better attributes such as texture, color and flavor, which came to employing non-parametric multiple comparisons. Jellies brands chosen for this work are the most Trujillano commercial market, which are Koky, Bold and Royal, they were evaluated for 30 sensory potential consumers using hedonic scale of 5 points. Test was applied Friedman's multiple comparison test and Wilcoxon signed rank. The data were processed in SPSS 15 and Excel. The Friedman test established both on the texture difference (p = 0.000 <0.05) and in color (p = 0.000 <0.05) and taste (p = 0.000 <0.05) between the gelatin Koky leading brands in the attribute texture and Gelati bold in color and flavor attributes, multiple comparison tests showed similarities in bold Koky gelatin compared to gelatin did not rust much acceptance by the judges. ease of application of nonparametric methods for multiple comparisons by ranks to extend its use in sensory evaluation of products in development and commercial process.